A Biodiversity Perspective on the NTFP Potential of Bilaspur forest Division of Chhattisgarh - Tiwari, S. C.; Itoo, Mukhtar Ahmad (Indian Forester, 2014)
The present paper deals with the various uses of plants species collected by the Baiga tribe in four selected forest villages of Bilaspur Forest Division. The information on collection, harvesting, marketing and sale of NTFPs were collected through personal interview with local elderly tribal people of the villages. During the study 24 wild edible and 19 medicinal plant species were found being utilized as food, medicine, fruits and for other purposes. The knowledge on plant resource use was observed to be location specific. The activities relating to the collection, harvesting, processing and sale of NTFPs are mainly performed by local tribal people living in the area. Interpretation of outstanding traditional knowledge on sustained harvesting, utilization and cultivation may further sustain their livelihoods. Characterization of plant based knowledge and refinement and value addition to bio- products may further advance the livelihood regime of the Baiga tribes living in the forest villages of Bilaspur Forest Division of Chhattisgarh.